ANALISIS KENAIKAN BPJS KESEHATAN TERHADAP PELAYANAN KESEHATAN MASYARAKAT DI PUSKESMAS TELADAN KECAMATAN MEDAN KOTA - Majid Dalimunthe; Zainuddin Nasution (STKIP PGRI TULUNGAGUNG, 2022)
This study aims to analyze the increase in the rate of BPJS health for public health services at model health centers. by using five dimensions of health service quality, namely: Reability, Tangibles, Responsiveness, Assurance, Empathy. The research location is at the model health center in the Medan City sub-district. The sample in this study amounted to ten informants. That this research uses descriptive method. Based on the results of research and data analysis from respondents from the five dimensions of the quality of public services that were determined, good results were obtained. The quality of health services at the puskesmas on the dimension of reliability provides services accurately or without errors, on the tangible dimension of service quality in the neatness of the officer's discipline. and on the responsiveness of the puskesmas employees who greet each patient and patient's family from the assurance point of the officers who serve in a friendly manner and can create a good first impression for the patients and visitors to the puskesmas, from the empathy of the puskesmas an exemplary service provided to each patient in accordance with the mission of the puskesmas to his patients.